2014
DOI: 10.1021/om500854u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Phosphonates to Phosphine Oxides: An Improved Synthetic Route to Phosphines Including the First Synthesis of Methyl JohnPhos

Abstract: I.General Considerations Unless stated otherwise, reactions were conducted in oven-dried glassware under an atmosphere of nitrogen. Diethylether and tetrahydrofuran were dried using a DriSolv system using CuO and molecular sives under argon, all other reaction solvents were purified and dried according to literature. 1 All commercially obtained reagents were used as received unless otherwise specified. Organomagnesium reagents synthesized were titrated before use using either diphenylacetic acid 2 or no-d NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…All phosphines but L16 and L9 can be produced on gram‐scale runs in 50–60 % yields, hence comparable to those given originally for dialkylbiaryl analogues and for the recently prepared PMe 2 Ar′ (Methyl‐JohnPhos; ca. 52 % three‐step overall yield) . With the exception of PEt 2 ArXyl2 , L16 , reported to form in unexpected low yields (about 40 %), it can be noticed that sterically demanding R groups provoke a significant decrease in isolated yields, which remain in the 35–60 % range for i Pr, c ‐C 5 H 9 and c ‐C 6 H 11 , in contrast with the 70–80 % values of the PMe 2 Ar′ analogues.…”
Section: Resultsmentioning
confidence: 93%
“…All phosphines but L16 and L9 can be produced on gram‐scale runs in 50–60 % yields, hence comparable to those given originally for dialkylbiaryl analogues and for the recently prepared PMe 2 Ar′ (Methyl‐JohnPhos; ca. 52 % three‐step overall yield) . With the exception of PEt 2 ArXyl2 , L16 , reported to form in unexpected low yields (about 40 %), it can be noticed that sterically demanding R groups provoke a significant decrease in isolated yields, which remain in the 35–60 % range for i Pr, c ‐C 5 H 9 and c ‐C 6 H 11 , in contrast with the 70–80 % values of the PMe 2 Ar′ analogues.…”
Section: Resultsmentioning
confidence: 93%
“…54,55 A recent development in our laboratory showed that direct and high-yielding P-C functionalization at phosphonates was possible without decomposition or the need for multistep chlorination. 56 In a typical reaction of a Grignard reagent with phosphonate, a pentavalent phosphorus intermediate quickly reacts with free halide in solution to form coordination salt oligomers (Scheme 10, top route). This reaction is mechanistically similar to the Michaelis-Arbuzov reaction and accounts for the complete consumption of phosphonate starting material and low yields of phosphine oxide.…”
Section: Phosphorus(v) Electrophilesmentioning
confidence: 99%
“…The development of synthetic routes to tertiary phosphines via air-stable intermediates and easier workups has been of great interest to our research group [31,32]. In this work, we demonstrate the synthesis of unsymmetric bidentate phosphines utilizing air-stable phosphine oxide starting materials and intermediates.…”
Section: Introductionmentioning
confidence: 99%